2018
DOI: 10.1080/02656736.2018.1440014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-treatment with gonadotropin-releasing hormone analogue GnRH-α on high-intensity focussed ultrasound ablation for diffuse adenomyosis: a preliminary study

Abstract: The combination of HIFU with GnRH-α is more effective than HIFU alone for ablation of diffuse adenomyosis. Moreover, the GnRH-α pre-treatment with HIFU is safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Moreover, five studies reported adverse reactions after treatment (11,13,14,17,19), of which only two (17, 19) completely and uniformly reported specific data of the type and number of adverse reactions in the two groups. The results of the two articles indicated no statistically significant difference in the incidence of adverse reactions between the experimental and control groups (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, five studies reported adverse reactions after treatment (11,13,14,17,19), of which only two (17, 19) completely and uniformly reported specific data of the type and number of adverse reactions in the two groups. The results of the two articles indicated no statistically significant difference in the incidence of adverse reactions between the experimental and control groups (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-nine full-text were assessed eligible, however, 60 were excluded for different reasons (11 articles' follow-up time were shorter than 3 months, 13 articles did not report recurrence, 17 articles were lack of other outcome indicators, and 19 articles had no control group). Nine studies with data for 766 patients were finally included in the present meta-analysis (11)(12)(13)(14)(15)(16)(17)(18)(19). The literature screening process is shown in Figure 1.…”
Section: Selected Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations